Government regulatory policy towards the Biopharmaceutical sector: regulatory outlook on biosimilars in Egypt. - Abdelhakim Farag, Mohamed Atef (AUC Knowledge Fountain, 2013)
The thesis examines the government regulatory policy towards the pharmaceutical biotechnology sector (Biopharmaceutical), with focus on Similar Biotherapeutic Products (biosimilars). Biosimilars are highly similar but not identical molecules that claim to have similar quality, safety and efficacy of original (innovator/ reference) products. They differ significantly from the chemical based medicines (conventional pharmaceuticals) that the main active substance is usually from a living organism (biological). Such critical products are high on the treatment guidelines recommended for complex diseases with high death and disability burdens. Biosimilars started accessing the Egyptian Market long time before the Government established a proper regulatory structure/pathway to regulate such products. It is expected that Biosimilars will start accessing the Egyptian market with high influx rate during the upcoming years as many originator biopharmaceuticals are losing patent protection between 2013-2020. Such influx requires progressive policy thinking and well-resourced regulatory structures to properly regulate the complex pharmaceutical biotechnology market, ensure protection of public health, prevention of potential regulatory failures and promoting investment in local production for improving access to medicines. The thesis adopts a qualitative methodology using semi structured and in-depth interviews with experts from the concerned governmental regulatory agencies, the biopharmaceutical industry, special interest groups (lobbying bodies), clinicians, civil society and independent researchers. Analytical findings revealed potential for regulatory reforms and policy options were suggested across the three regulatory domains studied (regulatory pathway of biosimilars , pricing policy and intellectual property protection).